Tobacco-derived and tobacco-free nicotine cause differential inflammatory cell influx and MMP-9 in mouse lung - Thomas Lamb; Gagandeep Kaur; Irfan Rahman (Respiratory Research, 2024)
Abstract Background Electronic nicotine delivery systems (ENDS) or electronic cigarettes (e-cigarettes) aerosolize an e-liquid composed of propylene glycol (PG) and vegetable glycerin (VG) as humectants, flavoring chemicals, and nicotine. Nicotine naturally occurs in two isomers R- and S-nicotine, with tobacco-derived nicotine (TDN) composed of S-nicotine, and tobacco-free/synthetic nicotine (TFN) composed of a racemic mixture of R- and S-nicotine. Currently, there is limited knowledge of the potential differences in the toxicity of TFN versus TDN. We hypothesized that exposure of TFN and TDN salts to C57BL/6J mice would result in a differential response in lung inflammation and protease/ antiprotease imbalance. Methods Five-week-old male and female C57BL/6J mice were exposed to air, PG/VG, PG/VG with TFN salts (TFN), or PG/VG with TDN salts (TDN) by nose-only exposure. Lung inflammatory cell counts, cytokine/chemokine levels, and matrix metalloproteinase (MMP) protein abundance and activity levels were determined by flow cytometry, ELISA, immunoblotting, and gel zymography, respectively. Results Exposure to the humectants (PG/VG) alone increased cytokine levels- IL-6, KC, and MCP-1 in the BALF and KC levels in lung homogenate of exposed mice. While no change was observed in the cytokine levels in lung homogenate of TDN aerosol exposed mice, exposure to TFN aerosols resulted in an increase in KC levels in the lungs of these mice compared to air controls. Interestingly, exposure to TDN aerosols increased MMP-9 protein abundance in the lungs of female mice, while exposure to TFN aerosol showed no change. The metabolism of nicotine or the clearance of cotinine for TFN exposure may differ from that for TDN. Conclusion Exposure to humectants, PG/VG alone, induces an inflammatory response in C57BL/6J mice. TFN and TDN salts show distinct changes in inflammatory responses and lung proteases on acute exposures. These data suggest variable toxicological profiles of the two forms of nicotine in vivo. Future work is thus warranted to delineate the harmful effects of synthetic/natural nicotine with humectants to determine the potential toxicological risks for users.